Exosomal MiR‐500a‐3p promotes cisplatin resistance and stemness via negatively regulating FBXW7 in gastric cancer. Issue 16 (25th June 2020) - Lin, Hao; Zhang, Liang; Zhang, Caihua; Liu, Pengpeng
Abstract: Chemoresistance has been a major challenge in advanced gastric cancer (GC) therapy. Exosomal transfer of oncogenic miRNAs implicates important effects in mediating recipient cell chemoresistance by transmitting active molecules. In this study, we found that microRNA‐500a‐3p was highly expressed in cisplatin (DDP) resistant GC cells (MGC803/DDP and MKN45/DDP) and their secreted exosomes than that in the corresponding parental cells. MGC803/DDP‐derived exosomes enhance DDP resistance and stemness properties of MGC803 recipient cells via exosomal delivery of miR‐500a‐3p in vitro and in vivo through targeting FBXW7. However, reintroduction of FBXW7 in MGC803 cells reverses miR‐500a‐3p‐mediated DDP resistance as well as stemness properties. Furthermore, elevated miR‐500a‐3p in the plasma exosomes of GC patients is correlated with DDP resistance and thereby results in poor progression‐free prognosis. Our finding highlights the potential of exosomal miR‐500a‐3p as an potential modality for the prediction and treatment of GC with chemoresistance.